2015
DOI: 10.1121/1.4927411
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing speech learning by combining task practice with periods of stimulus exposure without practice

Abstract: Language acquisition typically involves periods when the learner speaks and listens to the new language, and others when the learner is exposed to the language without consciously speaking or listening to it. Adaptation to variants of a native language occurs under similar conditions. Here, speech learning by adults was assessed following a training regimen that mimicked this common situation of language immersion without continuous active language processing. Experiment 1 focused on the acquisition of a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…In previous investigations, Practice+Exposure training promoted learning on fine-grained discrimination tasks—auditory frequency discrimination (B. A. Wright, Sabin, Zhang, Marrone, & Fitzgerald, 2010) and visual orientation discrimination (Szpiro, Wright, & Carrasco, 2014)—and on speech tasks—acquisition of a non-native phonetic contrast (Wright, Baese-Berk, Marrone, & Bradlow, 2015) and adaptation to a foreign accent (Wright et al, 2015). Therefore, we suspected that it might aid learning on musical-interval perception as well.…”
Section: Introductionmentioning
confidence: 98%
“…In previous investigations, Practice+Exposure training promoted learning on fine-grained discrimination tasks—auditory frequency discrimination (B. A. Wright, Sabin, Zhang, Marrone, & Fitzgerald, 2010) and visual orientation discrimination (Szpiro, Wright, & Carrasco, 2014)—and on speech tasks—acquisition of a non-native phonetic contrast (Wright, Baese-Berk, Marrone, & Bradlow, 2015) and adaptation to a foreign accent (Wright et al, 2015). Therefore, we suspected that it might aid learning on musical-interval perception as well.…”
Section: Introductionmentioning
confidence: 98%
“…It may be that this paradigm would be more effective in conjunction with training tasks where participants can explicitly practice on the tasks that will ultimately be used to assess learning. Indeed, in a recent study of non-native phonetic learning, Wright, Baese-Berk, Marrone & Bradlow (2015) found that alternating between periods of stimulus exposure and periods of explicit practice with posttest tasks yielded better learning than did explicit practice alone.…”
Section: Experiments 2: Discussionmentioning
confidence: 99%
“…Wright et al (2015) have recently suggested that a combination of paradigms with high and low engagement may be most effective. Training may focus on phonemelevel, word-level, or sentence-level contrasts, each of which may involve different cognitive processes and facilitate different types of learning.…”
Section: B Auditory Training Paradigmsmentioning
confidence: 99%
“…As described earlier, training paradigms may vary in duration, stimulus characteristics, blocking of stimuli, and participant engagement. Wright et al (2015) examined a training paradigm that combines both active training and passive exposure-only conditions, and concluded that this hybrid paradigm is more beneficial than either type of training alone. These authors also suggested that effective training can occur only when a sufficient amount of daily practice is achieved, and that benefits of training may be greatest when such practice is maintained, stimulating sustained neural plasticity.…”
Section: E Benefits Of High Variability Training Stimulimentioning
confidence: 99%